P12.03 How accurate and comprehensive are currently available mobile medical applications (apps) for sexually transmitted and genital infections: a comprehensive review. (13th September 2015) - Gibbs, J; Gkatzidou, V; Tickle, L; Manning, SR; Tilakkumar, T; Hone, K; Ashcroft, RE; Sonnenberg, P; Sadiq, ST; Estcourt, CS
Abstract : Introduction: In the UK, 88% of young people, a group at high risk of STIs, own a smartphone. Seeking sexual health advice online is common and provision of STI apps is increasing. The UK lacks a robust framework for quality control of mobile medical apps and potential for misinformation is substantial. We undertook a comprehensive review of content and accuracy of contemporary apps for STIs (except HIV) and related genital infections aimed at members of the public. Methods: Search of Googleplay and iTunes stores for free and paid apps regarding STIs and genital infections, testing, diagnosis and management, between 10/09/2014–16/09/2014. We assessed eligible apps against: 1) 19 modified Health on The Net (HON) Foundation principles; 2) comprehensiveness and accuracy of information on individual STIs/genital infections, and their diagnosis and management, compared with respective National Health Service STI information webpage content. Results: 144/6642 apps met eligibility criteria (Android n = 94; iOS n = 29; both n = 24). 57 were excluded after downloading. 87 apps (52 Android, 20 iOS, 15 both) were analysed. Only 29% apps met >/= 6 HON criteria. Content was highly variable: 34/87 (39%) covered one or two infections; 16/34 (47%) were ebooks, predominately about genital herpes or candidiasis; 40/87 (46%) covered multiple STIs; 5/87 (6%), solely focused on accessing STI testing. In terms of accuracy: 13/87 (15%) were fully, 46/87 (53%) mostly and 28/87 (32%) partially accurate. 25/87 (29%) contained >/= 1 instance of potentially harmful information. Apps available on both platforms had a greater degree of accuracy than single platform apps. Only 1 app provided fully accurate and comprehensive information on chlamydia. Conclusion: The marked variation in content, quality and accuracy of available smartphone apps combined with the relatively high proportion that contain harmful information, significantly risks undermining the potential health benefits of an e-health approach to sexual health promotion and information. Disclosure of interest statement: Nothing to declare.